Biochemical changes in banana fruits due to postharvest fungal pathogens - Gawai, Sawant S. G. and D. U. (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The nutritional value of fruits chiefly depends on the quality and quantity of nutritive substances. In the present investigation, four fungi were studied from banana fruits which cause considerable biochemical changes to alter the quality of banana fruit. The infected bananas showed a decrease in the quantity of total soluble sugar, protein, ash, ascorbic acid and mineral elements when compared with the control of fruit. B.theobromae, R.oryzae, G.musarum, A.niger, A.flavus and F.roseum were found to be associated with the ripening of bananas and also causes rot during storage.